KAJIAN KEBIJAKAN PENGENAAN CUKAI MINUMAN BERPEMANIS - Selvi, Selvi; Sitorus, Elisabet; Handayani, Siska; Maesiwi, Purwastuti (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2020)
The increase in diabetics due to sugary drinks needs to be controlled. The imposition of excise on sweetened drinks has been implemented in several countries. This study aims to examine the aspects of tax collection for sweetened drinks in Indonesia and their impact. The research method is qualitative research. The results showed that the imposition of excise on sweetened drinks could give impact on reducing consumption of sweetened drinks but give a negative impact on the economy.